2012
DOI: 10.5550/sgia.120802.en.100a
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Nutritional Knowledge and Food Habits of Collegiate and Non-Collegiate Athletes

Abstract: Nutrition is an important component of any physical fitness program. The main dietary goal for active individuals is to obtain adequate nutrition to optimize health fitness and to increase sports performance. The purpose of this study was to compare nutritional knowledge and food habits in collegiate s and non-collegiate athletes. The target population of this study was all male and female collegiate and non-collegiate athletes in Rasht city of Iran. After translate of the standard nutrition knowledge and atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Although, knowledge was comparable between male and female athletes competing at the same level (Arazi and Hosseini, 2012), suggesting that performance level may influence nutrition knowledge. The gender differences in nutrition knowledge between this study and pervious research may reflect confounding variables such as general education level, rather than gender 'per se'.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Although, knowledge was comparable between male and female athletes competing at the same level (Arazi and Hosseini, 2012), suggesting that performance level may influence nutrition knowledge. The gender differences in nutrition knowledge between this study and pervious research may reflect confounding variables such as general education level, rather than gender 'per se'.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, Jessri et al (2010) reported significantly higher nutrition knowledge for female athletes compared to male athletes. Whereas, Arazi and Hosseini (2012) reported significantly higher nutrition knowledge for male collegiate athletes compared to their non-collegiate female counterparts.…”
Section: Discussionmentioning
confidence: 82%
“…A 2014 review on the relationship between nutrition knowledge and dietary intake in adults also suggested that while the relationship between nutrition knowledge and dietary behavior appears to be moderate at best, results may be affected by the quality of measures used to assess knowledge [ 6 ]. Several studies assessing nutrition knowledge in athletes, not included in either of the aforementioned reviews, have been published in recent years [ 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The standard nutritional knowledge inventory developed by Zawila et al [1] was used for the study. Arazi and Hosseini [8] reported its reliability at 0.81 by using Cronbach's alpha. Nutritional behavior was tested by a questionnaire developed by Karegarfard et al [9], of which reliability was estimated at 0.86 using Cronbach's alpha.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, authors concluded that athletes did not have enough nutritional knowledge [3]. By evaluating nutritional knowledge of 250 collegiate and non-collegiate (130 male, 120 female) athletes, Arazi and Hosseini [8] found that nutritional knowledge of non-collegiate athletes is lower than collegiate athletes.…”
Section: Introductionmentioning
confidence: 99%